2008
DOI: 10.1507/endocrj.k07-082
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Expression of Alcohol Dehydrogenase Class I Gene in Rat Uterus and Its Up-regulation by Progesterone

Abstract: Abstract. The endometrium is one of the target tissues of the ovarian steroid hormones, estrogen and progesterone. In order to elucidate the mechanism of gene regulation in the endometrium, suppressive subtraction hybridization was performed to isolate the candidate genes controlled by progesterone in rat uterus. Alcohol dehydrogenase (ADH) class I gene was one of the candidate genes. Here we investigated the expression and regulation of ADH class I gene in rat uterus. The mRNA of ADH class I was detected in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Ohno et al have revealed the expression of ADH class I gene in rat endometrial stromal cells 7. Several reports have shown that the expression of the ADH class I gene is regulated by sex hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohno et al have revealed the expression of ADH class I gene in rat endometrial stromal cells 7. Several reports have shown that the expression of the ADH class I gene is regulated by sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…ADH and ALDH exist in multiple molecular forms that have been grouped into several classes 6. Recent data show that the uterus contains ADH class I, III, and IV isoenzymes 7. These enzymes also play a significant role in the metabolism of many biological substances.…”
Section: Introductionmentioning
confidence: 99%
“…The oxytocin receptor (Oxtr), receptor for the hormone and neurotransmitter oxytocin, has been found expressed in both myometrium and endometrium of uterus [43], [44]. ADH1 is specifically expressed in endometrial stromal cells, up-regulated by progesterone and may regulate retinoic acid synthesis [45].…”
Section: Discussionmentioning
confidence: 99%
“…To isolate the genes regulated by P 4 in the rat uterus, we previously performed suppressive subtractive hybridization (Ohno et al 2008), and 14-3-3t was identified as one of the genes that were upregulated in the rat uterus after P 4 treatment. The 14-3-3 proteins form a family of highly conserved molecules that are expressed in a wide range of organisms and tissues (Obsilová et al 2008).…”
Section: Introductionmentioning
confidence: 99%